Quality of antenatal care and its potential impacts on delivery services and postnatal care compliance among reproductive women in Bangladesh: A situation analysis from the Bangladesh Demographic and Health Survey 2017 - Mehejabin Nurunnahar; M. Pear Hossain; Tahmidul Haque; S. M. Rokonuzzaman; Susmita Dey Pinky; Rumpa Kairy; Tahrima Mohsin Mohona; Abdus Sobhan; Most. Hafeza Khatun; Abu Yousuf Md Abdullah; Md Shahjahan Siraj (PLoS ONE, 2025)
Background Ensuring quality antenatal care (ANC) and postnatal care (PNC) is crucial for reducing maternal and neonatal mortality rates. However, there are gaps in assessing the quality of ANC, leading to the proposal of standards by the World Health Organization. The study aims to examine the impact of quality ANC on delivery services and PNC compliance in Bangladesh using data from the Bangladesh Demographic and Health Survey (BDHS), providing insights for policymakers to improve maternal and neonatal health outcomes. Methods This study used data from 2017 Bangladesh Demographic and Health Survey (BDHS) to investigate the impact of quality antenatal care (qANC) on delivery services and PNC in Bangladesh. The study population included ever-married women aged 15–49 years who had experienced a recent pregnancy. The analysis assessed the relationship between qANC and facility delivery, skilled birth attendant (SBA)-assisted delivery, and PNC services within 48 hours of delivery. The study employed a two-stage stratified cluster sampling design, and data analysis was conducted using generalized linear models and considered various demographic and socioeconomic factors. Results Key findings include a low rate of qANC services (18%), with pregnancy-related counseling being the lowest component. About 82% received at least one ANC visit, but only 18.3% received a quality visit. Higher compliance with facility delivery (ARR: 1.3; 95% CI: 1.27–1.41), SBA-conducted delivery (ARR: 1.3; 95% CI: 1.24–1.35), and PNC services for both mother (ARR: 1.3; 95% CI: 1.24–1.35) and child (ARR: 1.3; 95% CI: 1.23–1.35) within 48 hours were observed when quality ANC was received. Factors such as completing secondary education, engaging in skilled/unskilled manual labor and higher wealth quintile were associated with better delivery and post-delivery outcomes. Conclusion Ensuring qANC and expanding PNC service use remain challenging in Bangladesh. Increasing the provision of qANC is crucial, as it is associated with higher adherence to PNC.